A preliminary checklist of mangrove plants and associate species in Sungai Kong Kong, Selat Medana, Johor, Malaysia - Mohd Amin, Ahmad Mukhlis; Shahari, Rozilawati; Kassim, Siti Zaleha; Che Amri, Che Nurul Aini; Ahmad, Zuhairi (International Network for Natural Sciences, 2020)
This paper attempts to provide a preliminary checklist of mangrove species in Sungai Kong Kong, Selat Medana, Johor. The results presented were taken from the sampling at Sungai Kong Kong. After being pressed, dried and mounted on herbarium sheet, the specimens were made into herbarium voucher. Of the 26 species, Rhizophora apiculata and R. mucronata are the dominant species in the mangrove forest of Sungai Kong Kong. This indicates that the mangrove forest of Sungai Kong Kong can potentially become an ecotourism site and should be conserved.